Estimation of Heat of Formation (?Hf) for Hydroxy-Terminated Polybutadiene - Gouranlou, Farideh (Asian Journal of Chemistry, 2010)
For estimation of heat of formation (ΔHf) of hydroxyterminated polybutadiene (HTPB), MNDO program was used. MNDO has restrictions in calculation large molecules, so we calculated ΔHf for segments and estimated it for mean chain of HTPB.